THE EFFICACY OF THE NEW DRUG FORM OF NIFEDIPINE WITH PROLONGED ACTION - NIFECARD-XL IN TREATMENT OF ARTERIAL HYPERTENSION - S. Yu. Martsevich; E. V. Alimova; V. M. Gorbunov; A. D. Deev; V. N. Hirmanov; L. A. Sokolova; V. I. Podzolkov; V. I. Karpov (Российский кардиологический журнал)
The efficacy of the new drug form of nifedipine with prolonged action - Nifecard-XL in treatment of arterial hypertension.